Measuring the effectiveness of the curriculum using program-objective gap analysis. - Esmeria, Giselle Joy C.; Carlos, Ma. Cecilia C.; Necesito, Miriam E.
The effectiveness of a school's engineering curricula can be measured by how much that school's programs are able to meet their objectives. The ability to meet objectives, likewise, measures, the quality of the programs. In order to improve competitiveness, a school's program objectives must be reviewed based on accepted academic standards. With the aim of a university to be globally competitive, a study is being conducted to assess its own programs against international accreditation criteria. This paper focuses only on the assessment of the Program Objectives particularly in the field of Industrial Engineering. The survey forms developed were used to determine the strengths and weaknesses of the program. The results of the study will be used to improve the current program and align it with international standards as part of the continuous improvemet activities of the department.
Keywords: Accreditation; Effectiveness; Program objectives; Effectiveness